THE EFFECT OF AUDIO VISUAL MEDIA-ASSISTED CONFERENCING APPROACH ON STUDENTS’ ABILITY TO WRITE NARRATIVE ESSAY AT GRADE V SD NEGERI 26 ARUNGKEKE, KABUPATEN JENEPONTO - Mila Karmila; Munirah, Tarman A. Arief (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine students’ ability to write narrative essays and to examine the significant effect of the conferencing approach assisted by audiovisual media for grade V students at SD Negeri 26 Arungkeke, Kabupaten Jeneponto. This research was a quasi-experimental study with a non-equivalent control group design. The results showed that the average pretest and posttest scores in the control class were 63.90 and 74.52, respectively, while in the experimental class they were 59.48 and 80.24. The N-Gain score in the control class averaged 0.24152, indicating low learning outcomes, whereas the experimental class averaged 0.4640, indicating moderate learning outcomes. The T-test results showed tcount = 2.283 > ttable = 0.021, and the two-tailed significance value was 0.030 < 0.05, indicating that Ho was rejected and Ha was accepted. Therefore, the conferencing approach assisted by audiovisual media had a significant effect on students’ narrative writing ability at grade V.